MODEL AKAD PEMBIAYAAN MURABAHAH PADA BANK SYARIAH INDONESIA - Rahman, Abdul (Fakultas Syariah (Syari'ah Faculty ), 2023)
This study aims to analyze the murabahah financing contract at the Ahmad Yani branch of the Bank Syariah Indonesia in Pontianak City. Murabahah is a form of buying and selling goods at a cost and profit taken by the seller must be conveyed to the buyer in detail and clearly. The problem in this study is how the subject and object of the murabahah financing contract at Bank Syariah Indonesia. In the study method used is normative legal research method, the data obtained are primary data, secondary data and the results of interviews with bank syariah Indonesia employees and murabahah financing contracts. The objects of this study are murabahah contracts, Bank Syariah Indonesia employees who know murabahah financing products, and regulations related to murabahah, whether it is the DSN-MUI fatwa on murabahah, as well as the Sharia Economic Law Compilation. The results of the research conducted by the researcher are the subject in the murabahah financing contract at the Islamic bank, namely the subject actor from the bank can be done by his staff, namely when doing the murabahah contract it can be signed by the marketing staff and the bank leadership is quite knowledgeable. The murabahah object in the murabahah financing contract at the Syariah Bank is not available at the time of the contract but is only given money, and the murabahah object is not fully controlled (not yet available). However, the bank represents the purchase of the murabahah object to the customer by means of a wakalah agreement to purchase it himself to a third party (supplier), and the bank only approves the customer's submission in the desired murabahah object.